Temperature Dependent Structural, Optical, Photocatalytic and Magnetic Properties of WO3 Nanoparticles - Shakun Saini; Manmeet Kaur; Chhavi Pahwa; Sonal Singh (Journal of Water and Environmental Nanotechnology)
Tungsten Oxide (WO3) nanoparticles have been prepared by hydrothermal method followed by the subsequent annealing at different temperature (200°C-400°C). The effect of annealing temperature on structural, morphological, optical, and magnetic properties of the prepared nanoparticles were investigated by XRD, FESEM, UV, FTIR and VSM respectively. The photocatalytic measurements were performed against methylene blue i.e. cationic dye under natural solar light. The XRD pattern confirms the formation of the WO3 phase without any secondary or impurities. The FTIR results confirm the functionalities of WO3 nanoparticles in the fingerprint and functional group regions. FESEM analysis revealed that the surface morphology of WO3 powder consists of spherical nanoparticles and EDS spectroscopy confirms the presence of tungsten and oxygen elements with perfect stoichiometry. The excellent degradation efficiency of about 94.8% of methylene blue has been achieved at highest calcination temperature i.e. 400 ℃. The VSM results show that WO3 exhibits higher coercivity and lower magnetization.